Ecstasy and me my life as a woman - Lamarr, Hedy 1914-2000 (Ishi Press International, 2014)
"They called her 'the most beautiful woman of the century', and in a decade when Hollywood still had superstars, she was a legend. These are Hedy Lamarr's uninhibited memoirs in which she conceals little about her six marriages and is outspoken about her hundreds of lovers" -- website